Preparation method of zinc sulfate carbon sulfide material and oxygen electro-catalysis application of zinc sulfate carbon sulfide material

The carbon sulfide material was prepared by zinc sulfate vulcanization method and combined with iron phthalocyanine, which solved the problem of poor stability of existing oxygen reduction catalysts, and achieved a catalyst with high oxygen reduction activity and stability, which was suitable for green energy conversion devices.

CN119430141APending Publication Date: 2025-02-14CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620788.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Existing oxygen reduction catalysts such as platinum-based catalysts have problems such as poor stability, high prices and scarce reserves, which are difficult to support the large-scale application of green energy conversion devices.

Method used

The carbon sulfide material was prepared by using zinc sulfate as the sulfur source by water grinding and high-temperature nitrogen flow, and iron phthalocyanine (FePc) was dispersed on the material to form catalysts such as FePc/CVDCS.

Benefits of technology

The oxygen reduction activity and stability of the catalyst are improved, the half-wave potential is better than that of commercial platinum carbon catalysts, and has a high specific surface area and porosity, which is suitable for electrocatalyst support.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430141A_ABST
    Figure CN119430141A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a zinc sulfate carbon sulfide material and application of the zinc sulfate carbon sulfide material as an oxygen electrocatalyst carrier. The preparation method comprises the following steps: firstly, preparing an ink dispersion liquid of a carbon material through a water milling method by utilizing the characteristics of good water solubility and high-temperature easy decomposition of zinc sulfate, and then carrying out high-temperature treatment to obtain a carbon sulfide material; experiments show that the sulfuration method not only can effectively dope sulfur element, but also can increase the specific surface area and porosity of the carbon material, and can be applied to various carbon materials. The sulfurized carbon material can be used as an oxygen electrocatalyst carrier, and shows better activity and stability than an unsulfurized carbon carrier. After the carbon material SVDCS prepared by the method is compounded with iron phthalocyanine (FePc), the obtained catalyst FePc / SVDCS has excellent oxygen reduction activity and stability, the half-wave potential is 0.91 V which is 70 mV higher than that of a commercial Pt / C catalyst, and the catalyst FePc / SVDCS has better stability, which shows that the carbon sulfide material has a good application prospect in the field of oxygen electrocatalyst carriers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy materials, and specifically relates to a method for preparing a sulfurized carbon material using zinc sulfate as a sulfur source, and also relates to the application of the carbon material loaded with iron phthalocyanine in the field of oxygen reduction electrocatalysis. Background Art

[0002] Power generation and energy storage through the electrochemical redox reaction of batteries is an effective, reliable and economical form of green energy. In these devices, oxygen reduction reaction (ORR) is a ubiquitous and critical step that directly affects the efficiency and performance of the battery. However, the kinetic process of ORR is relatively slow and usually requires the help of corresponding catalysts to complete the reaction. At present, precious metal-based catalysts such as platinum-based catalysts are considered to be the most effective oxygen reduction catalysts due to their excellent oxygen reduction activity, but they have problems such as poor stability, high prices, and scarce reserves, which are not enough to support the large-scale application of green energy conversion devices such as fuel cells. Therefore, the development of transition metal-based catalysts that are abundant in nature and have certain catalytic activity to replace platinum-based catalysts is regarded as one of the methods to achieve the widespread application of green energy. Among them, iron phthalocyanine (FePc) has precise Fe-N4 active sites, which can absorb and retain multiple electrons in the ORR process to optimize the binding energy of intermediates, thereby promoting the ORR reaction, and is considered to be an efficient ORR catalyst. However, FePc has low conductivity and is easy to aggregate. Therefore, dispersing FePc on a stable and conductive porous carbon support is a good strategy to improve the utilization of FePc.

[0003] Carbon carriers (such as graphene, carbon nanotubes, activated carbon, etc.) have high surface area, good electrical conductivity and chemical stability, which can effectively enhance the electrical conductivity and structural stability of the catalyst. The structure and chemical composition of the carbon carrier also directly affect the activity of the catalyst. Doping carbon materials with different elements (such as nitrogen, sulfur, phosphorus, etc.) can adjust their electronic structure to form sites with high catalytic activity, thereby improving the activity of oxygen reduction reaction. In view of the above background, this method uses zinc sulfate as a sulfur source, and utilizes the good water solubility and easy decomposition of zinc sulfate at high temperature to prepare a sulfur-doped carbon material. The carbon material is not only successfully doped with sulfur, but also has a higher specific surface area. After it is loaded with iron phthalocyanine, the resulting catalyst has better oxygen reduction activity and stability than undoped catalysts, showing that the sulfide carbon material has good application prospects in the field of electrocatalyst carriers. Summary of the invention

[0004] The invention provides a method for preparing a sulfurized carbon material using zinc sulfate as a sulfur source, and relates to application of the carbon material in the field of oxygen reduction electrocatalysis after the carbon material is loaded with iron phthalocyanine.

[0005] In order to successfully prepare the above-mentioned material, the following preparation method was adopted, comprising the following steps:

[0006] Step 1: Dissolve 0.7 g zinc sulfate in about 3 ml aqueous solution, put into a glass mortar, add 0.3 g carbon material in small amounts several times, and use a water grinding method to fully grind the carbon material in the zinc sulfate aqueous solution to obtain an ink dispersion.

[0007] Step 2: The dispersion was transferred into a porcelain boat and heated at 900° C. for 1 hour in a tubular furnace under nitrogen flow to obtain a heat-treated carbon material.

[0008] Step 3: The heat-treated carbon material was acid-washed with a 0.5 mol / L H2SO4 solution at 60°C for 2 hours, then washed and filtered until the filtrate was neutral, and dried in a vacuum oven for 12 hours to obtain sulfide carbon material I.

[0009] Step 4: Ultrasonic dispersion of Ⅰ and FePc in N,N-dimethylformamide (DMF) at a mass ratio of 5:1, stirring for 24 hours after sufficient dispersion, filtration and washing with DMF and anhydrous ethanol, and drying in a vacuum oven for 12 hours to obtain catalyst Ⅱ prepared by sulfided carbon material loaded with FePc. Comparative catalyst Ⅲ was prepared by compounding unsulfided carbon material with FePc using the same method.

[0010] In the present invention, in order to ensure the universal applicability of the sulfurization method, three carbon materials were selected for verification, namely, rod-shaped carbon material (CVDC), carbon black (CB), and carbon nanotubes (WCNT) prepared by chemical vapor deposition. Among them, CVDC is prepared in the laboratory, and is a rod-shaped carbon material prepared by vapor deposition of the precursor acetylene under the condition of nickel cobalt oxide as a catalyst. Therefore, the sulfurized carbon material I in the above experimental steps refers to sulfurized rod-shaped carbon material, sulfurized carbon black, and sulfurized carbon nanotubes, which are named CVDC, WCNT, and WCNT, respectively. S CB S , and WCNT S Ⅱ refers to the catalyst prepared by combining three carbon sulfide materials with FePc, named FePc / CVDC S 、FePc / CB S and FePc / WCNT S III refers to the comparative catalysts prepared by compounding unsulfurized carbon materials with FePc, and are named FePc / CVDC, FePc / CB, and FePc / WCNT.

[0011] The present invention provides an oxygen reduction working electrode. The above-synthesized catalyst samples II and III are dispersed in a 5% volume fraction Nafion anhydrous ethanol solution, the materials are dispersed evenly by ultrasound, and dropwise dripped on the surface of a dry rotating disk electrode (diameter 5 mm), and after natural drying, the electrochemical catalytic performance of the samples is tested.

[0012] The beneficial effects of the present invention are: (1) Using zinc sulfate as the sulfur source, the carbon material is fully ground in a zinc sulfate solution by a water mill to prepare a water-ink dispersion, and then heated at high temperature under nitrogen flow to prepare a sulfide carbon material. This process is simple to operate, the raw materials are easily available, and the method is applicable to a variety of carbon materials. (2) After sulfidation using this method, the carbon material is successfully doped with the S element and the specific surface area is significantly increased. (3) After being compounded with iron phthalocyanine, the oxygen reduction performance of the catalyst prepared from the unsulfurized carbon material is significantly improved. (4) The catalyst prepared in the present invention has the characteristics of high oxygen reduction electrochemical performance, high stability, and simple preparation method. FePc / CVDC S The half-wave potential of the catalyst is 0.91 V vs. RHE, which is better than that of commercial platinum-carbon catalyst (0.84 V vs. RHE); the stability is also better than that of commercial platinum-carbon catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0014] Figure 1 This is an image of the ink dispersion prepared in Example 1.

[0015] Figure 2 The CVDC and CVDC prepared in Example 1 S Scanning electron microscope image of

[0016] Figure 3 This is a scanning electron microscope element mapping of the CVDC prepared in Example 1.

[0017] Figure 4 The CVDC prepared in Example 1 S Scanning electron microscope elemental mapping.

[0018] Figure 5 The CVDC and CVDC prepared in Example 1 S Specific surface area and porosity distribution diagram.

[0019] Figure 6 CB and CB prepared in Example 1 S Specific surface area and porosity distribution diagram.

[0020] Figure 7The CNT and CNT prepared in Example 1 S Specific surface area and porosity distribution diagram.

[0021] Figure 8 The FePc, CVDC, CVDCS, FePc / CVDC and FePc / CVDC in Example 2 S X-ray diffraction pattern of .

[0022] Fig. 9 It is the FePc / CVDC prepared in Example 2 S Scanning electron microscope imaging (mapping)

[0023] Fig.10 This is the cyclic voltammetry curve of the catalyst after the three carbon sulfide materials and FePc are composited in Example 3.

[0024] Fig.11 It is the linear scanning curve of the three groups of catalysts in Example 3 at a rotation speed of 1600 rpm in an electrolyte solution saturated with O2 (0.1 M KOH).

[0025] Fig.12 These are the stability test curves of FePc / CVDC, FePc / CVDCS and commercial platinum-carbon catalysts in Example 3. DETAILED DESCRIPTION

[0026] In order to further illustrate the present invention, the preparation method and application of carbon sulfide materials and corresponding catalysts are described in detail below in conjunction with embodiments.

[0027] Example 1: CVDC S Synthesis: Dissolve 0.7g zinc sulfate in about 3ml aqueous solution, put it in a glass mortar, add 0.3g CVDC in small amounts several times, grind it thoroughly with water mill to obtain ink dispersion. Then transfer the dispersion into a porcelain boat, heat it at 900℃ for 1 hour in a tube furnace under nitrogen atmosphere, and after cooling, pickle it with 0.5mol / L sulfuric acid solution at 60℃ for 2 hours, then wash and filter it with water until the filtrate is neutral, and dry it in a vacuum oven for 12 hours to obtain the sulfide carbon material CVDC. S .

[0028] Figure 1 It is an ink dispersion image prepared by the water grinding method. Figure 2 It is CVDC and CVDC S A scanning electron microscope image of the carbon material shows a rod-like shape; Figure 3 and Figure 4 They are CVDC and CVDC respectively. S Scanning electron microscope element distribution map (mapping), it can be found that CVDC SThe C, O, S, and N elements are evenly distributed in the CVDC. S The S content in the sulfidized product is 1.96%, while that in the CVDC is only 0.09%. Compared with CVDC, the S content increases significantly after sulfidation, indicating that the zinc sulfate sulfidation method can effectively dope the S element. Figure 5 It is CVDC and CVDC S Specific surface area and porosity distribution diagram, Figure 6 It is CB and CB S Specific surface area and porosity distribution diagram, Figure 7 CNT and CNT S The specific surface area and porosity distribution diagram of Figure 5 , 6 7 It can be seen that the specific surface area of ​​the sulfurized carbon material is significantly increased compared with the unsulfurized carbon material, and the content of micropores and mesopores is significantly increased. The above results show that the sulfurized carbon material prepared by this method can not only effectively dope the S element, but also effectively increase the specific surface area and porosity, and has obvious advantages when used as an electrocatalyst carbon carrier.

[0029] Example 2: FePc / CVDC S Synthesis: 5 mg FePc was dissolved in 200 ml DMF by ultrasonication for 30 min, and then 25 mg CVDC was added S Continue ultrasonication for 1 hour until CVDC S The dispersed solution was stirred at room temperature for 24 hours to allow FePc and CVDC to S The composite catalyst FePc / CVDC was obtained by π-π interaction. S At the same time, the comparative sample FePc / CVDC was prepared by the same method.

[0030] Figure 8 FePc, CVDC, CVDC S , FePc / CVDC and FePc / CVDC S The X-ray diffraction (XRD) spectrum of FePc shows obvious crystal diffraction peaks near the small angle region, CVDC and CVDC S There are two broad peaks near 2θ = 25° and 43°, corresponding to the (002) and (101) diffraction planes of the graphite structure, respectively. S The crystallization peak of FePc does not appear in the XRD spectrum, and the basic peak shape of the carbon material is still maintained, indicating that no aggregation of FePc occurs in the catalyst. Fig. 9 FePc / CVDC SFrom the scanning electron microscope element mapping, it can be found that Fe, C, O, S, and N elements are evenly distributed. Combined with the XRD image, it can be explained that FePc is successfully dispersed and composited.

[0031] Example 3: Preparation of oxygen reduction working electrode: The synthesized catalysts were dispersed in a 5% by volume Nafion anhydrous ethanol solution, and the materials were evenly dispersed by ultrasound. 5 μL was dropped dropwise on a dry rotating disk electrode (diameter 5 mm). After natural drying, 5 μL was dropped dropwise on the electrode surface. After natural drying, the electrochemical catalytic performance of the sample was tested.

[0032] Fig.10 The cyclic voltammograms of the catalysts composited with three carbon sulfide materials and FePc are as follows. In a 0.1 mol / L KOH electrolyte solution saturated with N2, the cyclic voltammogram in the voltage range of 0.2 to 1.0 V is rectangular (as shown by the dotted line in the figure), and there is no obvious reduction peak. In a 0.1 mol / L KOH electrolyte solution saturated with O2, an obvious characteristic peak of oxygen reduction reaction appears (as shown by the solid line in the figure), indicating that these catalysts have significant electrocatalytic activity for oxygen reduction reaction. Fig.11 The linear scanning curves of the three groups of catalysts at 1600 rpm in an electrolyte solution saturated with O2 (0.1 mol / L KOH) are compared. The results show that FePc / CVDC and FePc / CVDC S The half-wave potentials of FePc / CB and FePc / CB are 0.87V and 0.90V respectively; S The half-wave potentials of FePc / WCNT and FePc / WCNT are 0.87V and 0.89V respectively. S The half-wave potentials of FePc and sulfided carbon are 0.89 V and 0.90 V, respectively, indicating that the oxygen reduction activity of FePc and sulfided carbon materials is significantly improved compared with unsulfided carbon materials. The catalysts prepared in the present invention all show a higher half-wave potential (0.84 V) than 20 wt% commercial platinum carbon. Fig.12 FePc / CVDC, FePc / CVDC S Stability test curve of commercial platinum carbon catalyst, FePc / CVDC S Compared with FePc / CVDC and commercial platinum carbon catalysts, it has higher stability. The above results show that the sulfide carbon material prepared by this method can effectively improve the activity and stability of the catalyst when used as an electrocatalyst carrier.

[0033] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician familiar with the profession can smoothly implement the present invention according to the drawings and the above description. However, any technician familiar with the profession can make some changes, modifications and equivalent changes made by using the technical content disclosed above without departing from the scope of the technical solution of the present invention, which are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the implementation technology of the present invention are within the protection scope of the technical solution of the present invention.

Claims

1. Obtaining a carbon material vulcanized with zinc sulfate as a sulfur source comprises the following steps: (1) Dissolve 0.7 g of zinc sulfate in about 3 ml of aqueous solution, put into a glass mortar, add 0.3 g of carbon material in small amounts several times, and grind thoroughly with a water mill to obtain a water-based ink dispersion of the carbon material. (2) The dispersion was transferred into a porcelain boat and heated at 900° C. for 1 hour in a tubular furnace under nitrogen flow to obtain a heat-treated carbon material. (3) The heat-treated carbon material was acid-washed with a 0.5 mol / L sulfuric acid solution at 60°C for 2 hours, then washed with water and filtered until the filtrate was neutral, and dried in a vacuum oven for 12 hours to obtain a sulfide carbon material.

2. The preparation method according to claim 1, characterized in that The sulfur source used in step (1) is zinc sulfate.

3. The preparation method according to claim 1, characterized in that: The method for preparing the dispersion is water grinding.

4. The preparation method according to claim 1, characterized in that: Compared with the unsulfurized carbon material, the sulfide carbon material prepared by this method is successfully doped with the S element and the specific surface area is also significantly increased.

5. The preparation method according to claim 1, characterized in that: This method is applicable to a variety of carbon materials, and currently verified carbon rods (CVDC), carbon black (CB), and carbon nanotubes (WCNT) prepared by chemical vapor deposition method.

6. The preparation method according to claim 1, characterized in that: The sulfide carbon material can be used as an electrocatalyst carrier and exhibits obvious advantages. S Catalyst FePc / CVDC prepared by compounding with iron phthalocyanine (FePc) S , compared with FePc / CVDC and commercial Pt / C catalysts, it has higher oxygen reduction catalytic activity and stability.